PowerPoint learning media to improve activeness and learning outcomes in the Economics subject - Indah Damayanti; Sukirno Sukirno (Curricula: Journal of Curriculum Development, 2025)
The number of learning media applied to each subject can have a significant impact on student development. Therefore, this study aims to analyze the application of interactive PowerPoint-based learning media in economics subjects and its effect on student learning outcomes. This research employs a literature review, collecting data from the Directory of Open Access Journals (DOAJ) to identify high-quality sources. Data analysis employs content analysis to yield valid results, ensuring clarity in the research findings. The results showed that the application of interactive PowerPoint-based learning media has been widely adopted in schools and has been successful in increasing student activity and learning outcomes in economics subjects. PowerPoint learning media with an attractive appearance and the ability to present audiovisual content can increase student involvement in the learning process, leading to interactions that support student engagement and enhance learning outcomes in economics subjects. In addition, the application of interactive PowerPoint-based learning media can streamline the learning process, making it easier for students to accept economic subject matter.   Abstrak Banyaknya media pembelajaran yang diterapkan pada setiap mata pelajaran dapat berdampak pada perkembangan peserta didik. Maka dari itu, penelitian ini bertujuan untuk menganalisis penerapan media pembelajaran berbasis PowerPoint interaktif pada mata Pelajaran Ekonomi dan pengaruhnya terhadap hasil belajar peserta didik. Penelitian ini menggunakan literature review dengan mengumpulkan data dari Directory of Open Access Journals (DOAJ) untuk mendapatkan sumber yang berkualitas. Analisis data menggunakan analisis isi untuk mendapatkan hasil yang valid sehingga tidak terjadi kekeliruan dalam hasil penelitian. Hasil penelitian menunjukan penerapan media pembelajaran berbasis PowerPoint interaktif telah banyak diterapkan pada sekolah-sekolah dan berhasil dalam meningkatkan keaktifan dan hasil belajar peserta didik pada mata pelajaran Ekonomi. Media pembelajaran PowerPoint dengan tampilan yang menarik dan dapat menyajikan audiovisual mampu meningkatkan keterlibatan peserta didik dalam proses pembelajaran sehingga terjadi interaksi yang mendukung keaktifan peserta didik dan meningkatnya hasil belajar mata pelajaran Ekonomi. Selain itu, penerapan media pembelajaran berbasis PowerPoint interaktif mampu mengefektifkan proses pembelajaran sehingga peserta didik mudah menerima materi pelajaran Ekonomi. Kata Kunci: Ekonomi; media pembelajaran; PowerPoint interaktif